Economic Competitiveness of Renewable Energy Pathways to 100% Global Coverage - Hoffmann, Winfried (Wiley, 2014)
The world is at the crossroads of either quickly changing the energy picture towards implementing efficient renewable energy sources or postponing this process by another generation.  Based on the author's more than 30 years industrial experience, this book gives a set of assumptions by extrapolating known technology developments and shows that 100% coverage by renewable technology of the global energy needs is much more probable than previously argued
Description based on publisher supplied metadata and other sources
Keywords: Energy industries; Energy policy; Renewable energy sources -- Economic aspects; Renewable energy sources; Energieversorgung; Erneuerbare Energien